2015
DOI: 10.1021/acs.analchem.5b01592
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Flow-Field Flow Fractionation Hyphenated ICP-MS as an Alternative to Cloud Point Extraction for Quantification of Silver Nanoparticles and Silver Speciation: Application for Nanoparticles with a Protein Corona

Abstract: Production and application of nanoparticles in consumer products is at an all-time high due to the emerging field of nanotechnology. Direct detection and quantification of trace levels of nanoparticles within consumer products is very challenging and problematic. Although multiple methodologies are available for this purpose, each method has its own set of limitations. Herein, we developed an analytical platform consisting of asymmetric flow-field flow fractionation (AF4) coupled with inductively coupled plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…Asymmetric flow field flow fractionation (AF4) is another popular technique in characterizing metallic and metal oxide NPs [11,12]. We previously reported a robust method using AF4 coupled with ICPMS for the online enrichment, speciation, and quantification of Ag + and NPs [13]. A detection limit as low as 0.004 μg kg −1 was achieved and the method also demonstrated its ability in analyzing bovine serum albumin (BSA) coated Ag NPs.…”
Section: Introductionmentioning
confidence: 99%
“…Asymmetric flow field flow fractionation (AF4) is another popular technique in characterizing metallic and metal oxide NPs [11,12]. We previously reported a robust method using AF4 coupled with ICPMS for the online enrichment, speciation, and quantification of Ag + and NPs [13]. A detection limit as low as 0.004 μg kg −1 was achieved and the method also demonstrated its ability in analyzing bovine serum albumin (BSA) coated Ag NPs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies, employing TEM to determine the size of the AuNPs 13 and AgNPs 16 , showed that the size was unaffected by CPE, even in the presence of acid. The redisolution of the surfactant-rich phase sample in alcohol after CPE may explain the observed difference with the current study (disaggregation).…”
Section: Resultsmentioning
confidence: 99%
“…10, 11 Single channel techniques such as field flow fractionation can also be utilized to pre-concentrate MNP samples; in this case, a large volume of sample is injected in the channel and the focusing step is extended. 12, 13 This method can be coupled online to appropriate detectors or concentrated fractions can be collected for off-line analysis. However, interactions can and do occur with the accumulation wall membrane due to the increased focusing time.…”
Section: Introductionmentioning
confidence: 99%
“…AF4 can be hyphenated with other techniques including ICP-MS, multi-angle light scattering and, UV-visible absorbance. Multiple applications of these hyphenated techniques have been demonstrated in recent literature reports [10,12,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%